Step One within Stepped Care Trauma-Focused Cognitive Behavioral Therapy for Young Children: A Pilot Study - Salloum, Alison (2014)
This pilot study explored the preliminary efficacy, parent acceptability and economic cost of delivering Step One within Stepped Care Trauma-Focused Cognitive Behavioral Therapy (SC-TF-CBT). Nine young children ages 3–6 years and their parents participated in SC-TF-CBT. Eighty-three percent (5/6) of the children who completed Step One treatment and 55.6 % (5/9) of the intent-to-treat sample responded to Step One. One case relapsed at post-assessment. Treatment gains were maintained at 3-month follow-up. Generally, parents found Step One to be acceptable and were satisfied with treatment. At 3-month follow-up, the cost per unit improvement for posttraumatic stress symptoms and severity ranged from $27.65 to $131.33 for the responders and from $36.12 to $208.11 for the intent-to-treat sample. Further research on stepped care for young children is warranted to examine if this approach is more efficient, accessible and cost-effective than traditional therapy.